The International and Political Journal: Japan according to regional role calculations - Tawfiq, Ghufran Abdul Karim (The International and Political Journal, 2024)
The Japanese experience is considered a unique experience of its kind. It was and still Is the focus of admiration for the whole world, and by virtue of the federal nature of this experience and its status, it enjoys multiple strengths, as Japan has become in second place in the world economically after the United States of America. The technological revolution has been embodied in all fields, and Japan has become a superpower among the eight major countries in the world.